Computational mechanism design for multi-sensor information fusion - Rogers, A; Dash, R; Jennings, N; Reece, S; Roberts, S (2006)
Conventional information fusion architectures are challenged by developments in sensor networks that allow individually-owned (and thereby selfish) sensors to interact and share data. Given this, we advocate the use of tools and techniques from computational mechanism design, a field at the intersection of computer science, game theory and economics, to address the challenges posed by these networks. These techniques allow us to engineer networks with desirable system-wide properties, in which sensors are represented as selfish rational agents, each attempting to fulfill their own individuals goals. In this paper, we present the work of the Argus II DARP project (http://www.robots.ox.ac.uk/~argus/) and we demonstrate the application of mechanism design within a real world information fusion sensor network scenario. Copyright 2006 ACM.